Fostering the Attitude of Tolerance Between Religious Comunity at The Al-Amin Mosque at the Resort Police of Baubau - Samsu, La (Room of Civil Society Development, 2022)
Religious tolerance is a relationship between religious communities based on mutual acceptance, mutual respect, respect for every difference, respect for equality in the practice of their religious teachings and work together in the life of society, nation and state. Tolerance actually develops within the framework of the existence of diversity in various dimensions of life, so that harmony and harmony in life can be realized, far from conflicts and social tensions, especially conflicts and hostility among each other in society. The method used during the activity was various lectures to provide understanding and convey theoretical concepts in order to help the congregation understand the nature of inter-religious tolerance at the Baubau Police Resort Al-Amin Mosque. The results of this service foster an attitude of tolerance in religious diversity that can be properly embedded because of the attitude of tolerance in society. The role of leaders and community leaders is very important in instilling an attitude of religious tolerance both through giving examples and through sustainable activities.